Texts and Traditions of Medieval Pastoral Care, Essays in Honour of Bella Millett : Essays in Honour of Bella Millett. - Gunn, Cate (Boydell & Brewer, 2009)
Pastoral and devotional literature flourished throughout the middle ages, and its growth and transmutations form the focus of this collection. Ranging historically from the difficulties of localizing Anglo-Saxon pastoral texts to the reading of women in l.